Assessment of Histopathological Alterations and Oxidative Stress in the Liver and Kidney of Male Rats following Exposure to Aluminum Chloride - Anfal Kadhim; Ahlem Ben Slima; Ghusoon Alneamah; Mohamed Makni (Journal of Toxicology)
The study aims to investigate the residual and histopathological effects of chronic aluminum chloride (AlCl3) toxicity in the kidney and liver of male rats. After 30-, 60-, and 90-day exposure period, analyses were conducted to assess the toxicity in the kidney and liver. The results showed that the concentration of AlCl3 in the kidney and liver increased significantly in 30-, 60-, and 90-day periods. The effects of oxidative stress on the kidneys and liver were dose- and time-dependent. Levels of malondialdehyde (MDA) significantly increased when exposed to AlCl3 groups. Conversely, the activity of antioxidant parameters, including reduced glutathione (GSH), catalase (CAT), and superoxide dismutase (SOD), significantly decreased in the AlCl3 exposed groups, indicating compromised oxidant mechanisms. Both the kidney and liver exhibited severe tissue damage, including necrosis, fibrosis, and inflammatory cell infiltration, in rats exposed to AlCl3. Kidney sections showed hyperplasia of the epithelial cells lining the renal tubules, resembling finger-like structures. Liver sections displayed severe lobular hyperplasia and an increase in mitotic figures. Our study suggests that AlCl3 has a detrimental impact on these vital organs and emphasizes the importance of monitoring and mitigating aluminum exposure, particularly where it is present in high concentration.